1977
DOI: 10.1099/00221287-98-1-147
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Mitochondria and Vacuoles of Candida utilis and Schizosaccharomyces pombe Studied by Electron Microscopy of Serial Thin Sections and Model Building

Abstract: The structure of mitochondria and of vacuoles in Candida utilis and Schizosaccharomyces pombe has been studied by electron microscopy of serial thin sections and subsequent model building. The models of the two cells of C. utilis which were studied confirmed our earlier findings, made by high voltage electron microscopy of thick sections, that there is a single, branched and continuous mitochondrial network in the cell (Davison & Garland, 1975). A model of a S. pombe cell showed that the mitochondrial structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…1-4). Consistent with previous observations by EM of serial thin sections (Davison & Garland, 1977) and by fluorescence microscopy (Benard & Karbowski, 2009), we also observed large portions of the mitochondrial network, confirming its presence. However, it was impractical to perform a montage of cryoelectron tomography due to the radiation damage caused by overexposure in the overlapping areas.…”
Section: Cryo-em Of Mitochondria In Intact Hela Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…1-4). Consistent with previous observations by EM of serial thin sections (Davison & Garland, 1977) and by fluorescence microscopy (Benard & Karbowski, 2009), we also observed large portions of the mitochondrial network, confirming its presence. However, it was impractical to perform a montage of cryoelectron tomography due to the radiation damage caused by overexposure in the overlapping areas.…”
Section: Cryo-em Of Mitochondria In Intact Hela Cellssupporting
confidence: 92%
“…In addition, understanding how binary fission occurs is challenged by the complexity of mitochondrial morphology and dynamics. It is well known that the majority of mitochondria in a cell form a huge interconnected network (Davison & Garland, 1977), which is highly dynamic (Lewis & Lewis, 1914) and undergoes continuous and frequent fission and fusion (Chan, 2006; Hoppins et al, 2007; Westermann, 2010; Youle & van der Blick, 2012). One of the potential challenges is to understand how this very large interconnected mitochondrial network accommodates binary fission, as binary fission would require the mitochondrial network to double in size before it divides into two equally sized daughter mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…This tendency also occurs during germ tube formation. However, while Tanaka et al have reported the occurrence of cell-cycle associated fusion and fragmentation of mitochondria in C. albieans [114], similar to other Candida species, e.g., C. utilis [23] and C. tropiealis [32], a recent fluorescence micrographic study by Ito-Kuwa et al does not demonstrate cell-cyle related morphological changes [45]. Rather it suggests that the form and number of mitochondria of C. albieans are primarily influenced by the physiological state of growth.…”
Section: Mitochondria During Cell Cyclementioning
confidence: 97%
“…Three‐dimensional reconstruction of cells from serial sections has been used for studying the complex architecture and dynamics of organelles in various species of yeast cells [1–8]. A single giant mitochondrion was reported in Saccharomyces cerevisiae [2], but other studies have shown multiple mitochondria and changes in the number and morphology at different stages of the cell cycle and under various growth conditions [3,5–8].…”
Section: Introductionmentioning
confidence: 99%